Urban Development and Female Convent Fundations in the Audiencia of Santa Fe and the Governement of Popayán (1575-1651) (2023)
Between 1575 and 1651, 13 convents were founded in a large part of what is now the territory of the Republic of Colombia. In this article, we analyse the links between these convents and the social and economic environment in which they arose. We aim to study how these institutions functioned as true sounding boards and alternatives to the needs of the social whole, which promoted them in a clear interaction of ideological, social, and economic factors.    This perspective attempts to be global and will, therefore, require an examination of regional contexts and their productive possibilities, capable of sustaining religious communities according to the regulations from the Council of Trent. This article approaches a broad historiographical base for a better contextualization of the documentary sources that reveal the beginnings of the convents. The varied bibliography and documents will support a deep and accurate analysis of the social links that the female religious institutions created between the 16th and 17th centuries, and the settlement processes linked to the emergence of female convents and their presence in the Castilianisation of the urban areas of the Audiencia of Santa Fe and the Government of Popayán.